The bootlegger [large type] : an Isaac Bell adventure - Cussler, Clive; Scott, Justin (Cussler, Clive. Isaac Bell novels, 2014)
"It is 1920, and both Prohibition and bootlegging are in full swing. When Isaac Bell's boss and lifelong friend Joseph Van Dorn is shot and nearly killed leading the high-speed chase of a rum-running vessel, Bell swears to him that he will hunt down the lawbreakers, but he doesn't know what he is getting into. When a witness to Van Dorn's shooting is executed in a ruthlessly efficient manner invented by the Russian secret police, it becomes clear that these are no ordinary criminals. Bell is up against a team of Bolshevik assassins and saboteurs--and they are intent on overthrowing the government of the United States"--